(untitled) (Global Journal of Human-Social Science, 2013)
This study conducted in Iran reports on research into perceptual learning style of medical sciences students generally and that of Students of Medicine SM and Anesthesiology SA in particular Results revealed that the students preferred learning styles were tactile and kinesthetic followed by visual and auditory but individual and group preferences were at the lowest Females of the two fields were stronger than males in 5 domains Female SM were better in all 6 areas of learning compared to female SA Male SA compared to their female peers however were better motivated and thus more oriented toward their field and future profession The findings can have some implications for curriculum development material development teacher training courses and class management Moreover by having an awareness of our students learning styles classes can be placed into homogeneous groups and expose each to their most preferred learning orientation and even work on and improve the learners least preferred styles from the other end of the continuum